Acute Oral Toxicity Evaluation of Extract Bajakah (Spatholobus littoralis Hassk) in Mice - Imran Firman; Safaruddin Safaruddin; Nurisrah Nurisrah; Besse Yuliana (Pharmaceutical Reports, 2023)
One potential biodiversity as traditional medicine is bajakah (Spatholobus littoralis Hassk.). Bajakah is an herbal plant that has been used in the Borneo region, Indonesia. However, there are not enough data regarding the toxicity of this plant. Therefore, in this study, we aimed to determine acute toxicity in the form of a lethal dose value of 50% (LD50) and the effect on behaviour and organ macroscopic after administration of S. littoralis methanol extract. The LD50 test used 50 male mice divided into five groups of 5 mice each. The treatment groups were divided based on the concentration of the given extract, namely; 0, 1, 10, 100, and 1000 mg/g BW. Observations were made for 14 days after treatment, and then surgery and macroscopic observations were made on the organs of mice. The results showed that the LD50 value for replication A and B was 17.78 and 68.13 mg/Kg BW, respectively. Macroscopic observations found damage to the liver, heart, and stomach. The macroscopic assessment by ANOVA and Kruskal Wallis test showed that in the replication A there was a toxic effect on the stomach, which was marked by a significant difference in weight compared to the control at the test level of p 0.05. These data revealed that the methanol extract of S. littoralis lignum is categorized as very toxic, and therefore, it requires special attention in its use. However, further research needs to be done to support the results of this study.